On the Consequences of Eliminating Capital Tax Differentials - Ctirad Slavik; Hakki Yazici (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In the United States structure and equipment capital are e ffectively taxed at different rates. Recently, President Obama joined the group of policy makers and economists who propose to eliminate these di erentials. This paper analyzes the consequences of such a reform using an incomplete markets model with equipment-skill complementarity. We fi nd that the reform increases average welfare by 0.1%. Importantly, we fi nd that the reform does not involve the usual effi ciency vs. equality trade-o ff: it improves both.
Keywords: E62; H21; H25; 330